TINJAUAN SOSIAL EKONOMIS PELAKU USAHA KECIL KELOMPOK PENERIMA BANTUAN PROGRAM PEL (Pengembangan Ekonomi Lokal) di Kecamatan Denpasar Timur - Puspa Yusuf, Ria (PIRAMIDA; Vol 3, No.2 Desember 2007)
The research aims to investigate social-economic impact of the program on the target group, as well as the obstacles faced in running the program.. Data were collected from 12 respondent consists of 6 member of Silver Crafte group and 6 member of Animals Farmer group. The data then were analysed descriptively.The results show that some social impact occures:(1) there is harmony in social relationship within the members of two group (98,25%), (2) the score of 25,50% reached in terms of social relationship between the group and surrounding society, and (3) a very low (33%) of social conflict, internally as well as externally.Meanwhile, in term of economic, the impact of the program on the silver craft group as follow: (1) capital are developed in amount of 6,43% in average, (2) the value of production increased by 6,65%, (3) the raise of income by 57,43%, (4) art-shop and export marketing and (5)labor absorbtion in amount of 32 people. The economic impact on animal farmer group are: (1) capital development average is 9,91%, (2) production value is 10,94 in average, (3) income development is 12,84% in average, (4) direct marketing of product, and (5) family labor absorbtion is 4 person in average.The problems faced by the first group are, difficulties in accessing capital, lack of technology and also lack of skill of the group member, as well as a difficulty in having a business partner. The second group also has some problem namely, lack of capital, lack of piglet quality, the expensive price of piglet as well as the feeding, unstabilised of selling price and difficulty of having a business partner.
Keywords: aspek sosial- ekonomis, pengembangan ekonomi lokal